A rapid validated HPLC method for determination of sulforaphane and glucoraphanin in broccoli and red cabbage prepared by various cooking techniques - ÇELİK, MELEK ŞİRİN (ROYAL SOC CHEMISTRY, 2014)
In this work, the effects of common cooking practices such as boiling, microwaving, steaming, and oven cooking and their influence on the amount and release of glucoraphanin (GCP) and sulforaphane (SFP) in broccoli and red cabbage were investigated using HPLC. These vegetables are approved for their beneficial effects and have preventing effects particularly against colon, lung, breast, and prostate cancers due to their glucosinolate content, therefore, development of an analytical method for determination of their glucosinolate profile is an important step in clinical studies. The HPLC method that is introduced in this study is fully validated and proved to be fast and effective. On the other hand, the importance of the methods of cooking these vegetables has been investigated and compared with each other that resulted in detecting SFP in all samples studied except in samples where whole broccoli was directly added into the boiled water.
Keywords: ELECTROKINETIC CAPILLARY CHROMATOGRAPHY; PERFORMANCE LIQUID-CHROMATOGRAPHY; SOLID-PHASE EXTRACTION; LUNG-CANCER RISK; CRUCIFEROUS VEGETABLES; ANTIOXIDANT ACTIVITY; BRASSICA VEGETABLES; THERMAL-DEGRADATION; HUMAN HEALTH; GLUCOSINOLATE